Clinical risk factors, emotional reactivity/regulation and suicidal ideation in elementary school-aged children. (June 2021) - Sheftall, Arielle H.; Vakil, Fatima; Armstrong, Sarah E.; Rausch, Joseph R.; Feng, Xin; Kerns, Kathryn A.; Brent, David A.; Bridge, Jeffrey A.
Abstract: Objective: Suicidal behavior (SB) in young children is rare yet in 2019, suicide was the fifth leading cause of death in 5-12-year-old youth. Understanding the risks associated with childhood suicidal ideation (SI) and SB will determine which factors should be targeted for prevention programming. This study examined clinical characteristics and emotional reactivity/regulation (ERR) in children with (SI+) and without (SI-) SI. Method: One hundred seventeen children, 6–9 years, and one biological parent were enrolled. Children completed interviews concerning SI/SB and parents completed interviews/self-reports about SI/SB, psychiatric distress, and history of abuse/neglect and their child's SI/SB, mental health, and ERR. Independent t-tests and Chi-square analyses using Bonferroni correction were conducted to examine SI group differences. Variables were then screened using forward stepwise logistic regression to determine association with SI + status. The final logistic regression included variables that survived screening procedures only. Results: Univariate analyses revealed SI + children were more likely to have a parental history of suicide attempt (PH+), higher rates of current psychotropic medication use, higher scores on the CBCL-DSM oriented scales (e.g., ADHD problems), and higher negative affect compared to SI- children. After analytic screening procedures, PH+, anxiety problems, ADHD problems, and anger survived. The final logistic regression revealed PH + status and anxiety problems were associated with SI + status. Conclusion: Long-term follow-up is needed to determine if these factors are predictive of a first-time suicide attempt in this at-risk group. Highlights: Examined characteristics associated with suicidal ideation (SI) in children. Differences on risk factors found between SI+ and SI- youth (e.g., parental history of suicide attempt (PH+)). Final logistic regression model revealed correlates of SI+ status were PH+ status and anxiety problems. Long-term follow-up is needed to determine if these factors are predictive of first-time suicide attempt.